A systematic approach to equity assessment for digital health interventions: case example of mobile personal health records. (12th June 2019) - Were, Martin C; Sinha, Chaitali; Catalani, Caricia
Abstract: Despite the increasing number of digital health interventions in low- and middle-income countries and other low-resource settings, little attention has been paid to systematically evaluating impacts of these interventions on health equity. In this article, we present a systematic approach for assessing equity impacts of digital health interventions modeled after the Health Equity Impact Assessment of the Ontario Ministry of Health and Long-Term Care. The assessment approach has 4 steps that address (1) scope, (2) potential equity impacts, (3) mitigation, (4) monitoring, and (5) dissemination strategies. The approach examines impacts on vulnerable and marginalized populations and considers various social determinants of health. Equity principles outlined by Whitehead and Dahlgren are used to ensure systematic considerations of all potential equity impacts. The digital health evaluation approach that is presented is applied to a case example of mobile personal health record application in Kenya.